EUPATI and Patients in Medicines Research and Development: Guidance for Patient Involvement in Ethical Review of Clinical Trials - Klingmann, Ingrid; Heckenberg, Andrea; Warner, Kay; Haerry, David; Hunter, Amy; May, Matthew; See, Wolf (Frontiers in Medicine, 2018)
Involvement of patients in the research and development process (R&D) of new medicines—in all areas of indications—today is a widely accepted strategy in pharmaceutical industry to ensure relevance and suitability of the treatment under development. This may consist in, but is not limited to, patient input to achieve more patient-friendly protocol design, endpoint, and comparator selection as well as disease-adapted study conditions in a pre- or post-marketing clinical trial. Ethical aspects and especially the balance of benefit and risk in a clinical trial are frequently judged differently by clinical researchers, regulators, ethics committees, and patients due to their different focus. The final assessment of the ethical aspects of a planned clinical trial is provided by an independent ethics committee consisting of physicians and other experts in healthcare and clinical trial methodology as well as of lay persons. The participation of patients in ethics committees is a much-discussed concept, its suitability disputed in many countries, and only limited experience on best practices is available. In order to be effective and yield the best results for all stakeholders, integration of patients into the medicines development process needs to be structured and governed by clear, mutually agreed rules and modes of operation. Communication and collaboration processes need to be systematically implemented to establish transparency, trust and respect between those developing new medicines and their users, respectively between those involved in design and approval of clinical trials and participants. In particular agreement on the ethical aspects of a clinical trial and/or its overall ethical acceptability is a prerequisite before the start of a clinical trial. Existing codes of practice for patient involvement with various stakeholders do not comprehensively cover the full scope of R&D, with the exception of more general statements on interaction. Overarching guidance on meaningful and ethical interaction is missing. One specific aim of the European Patients' Academy on Therapeutic Innovation (EUPATI) was to close this gap through the development of guidance documents for ethics committees, pharmaceutical industry-led medicines R&D, regulatory authorities, and health technology assessment (HTA). This EUPATI “Guidance for patient involvement in ethical review of clinical trials” gives practical recommendations for ground rules and lists options for conditions and practices for involving patients in the work of ethics committees to enable trustful and constructive collaboration whatever the national (legal) framework for patient involvement in ethics committees might be. The guidance sets the collaboration of patients in ethics committees in the broader context of relevance and opportunities for patient input on ethics in the overall medicines R&D and specifically the overall clinical trial process from concept development to trial result reporting in lay summaries. In addition to a presentation of the full text of the Guidance, this article aims at providing additional background information on the development process of the Guidance, as well as insight into the current debate on this topic.